The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11032-020-01192-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics analysis reveals the variations of eating quality among three high-quality rice cultivars

Abstract: Good eating quality is a highly desirable trait of rice which determines its commercial value and market share. However, the molecular basis of this trait remains largely unknown. Here, three high-quality conventional rice cultivars, including two superior eating quality cultivars Meixiangzhan-2 (MXZ) and Xiangyaxiangzhan (XYXZ), and one ordinary eating quality cultivar Huanghuazhan (HHZ), were analyzed by comparative metabolomics to identify the inherent mechanism for the formation of superior eating quality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Comparative metabolomics analysis has been used in several rice studies designed to improve rice quality and evaluate metabolome changes that may impact the nutritional content or therapeutic potential of different rice varieties [75][76][77][78]. In the metabolic profiling of GM rice lines transformed with insect-resistance genes, the study found three upregulated metabolites in the GM lines.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative metabolomics analysis has been used in several rice studies designed to improve rice quality and evaluate metabolome changes that may impact the nutritional content or therapeutic potential of different rice varieties [75][76][77][78]. In the metabolic profiling of GM rice lines transformed with insect-resistance genes, the study found three upregulated metabolites in the GM lines.…”
Section: Discussionmentioning
confidence: 99%
“…Rice grains have abundant metabolites, but there are few studies comparing metabolite differences among rice varieties with different taste qualities [25]. The taste quality and nu-tritional quality of milled rice are the key indicators used to measure the quality of a rice variety, and they are also good experimental materials to explore the mechanisms involved in the development of rice taste and nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…Rice is the staple food of more than half of China's population. The contents of nutrients and active substances in rice often vary with the variety ( Gong et al, 2020 , Chen et al, 2022 ). Purple rice grains are rich in vitamins, a large amount of trace elements, and polyphenols such as flavonoids and anthocyanins, which have specific health care functions ( Zhang, 2021 , Xiong et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%